Hydroperoxyl Radicals (HOO.): Vitamin E Regeneration and H‐Bond Effects on the Hydrogen Atom Transfer. Issue 46 (6th October 2016) - Cedrowski, Jakub; Litwinienko, Grzegorz; Baschieri, Andrea; Amorati, Riccardo
Abstract: Hydroperoxyl (HOO . ) and alkylperoxyl (ROO . ) radicals show a different behavior in H‐atom‐transfer processes. Both radicals react with an analogue of α‐tocopherol (TOH), but HOO ., unlike ROO ., is able to regenerate TOH by a fast H‐atom transfer: TO . +HOO . →TOH+O2 . The kinetic solvent effect on the H‐atom transfer from TOH to HOO . is much stronger than that observed for ROO . because noncovalent interactions with polar solvents (Solv⋅⋅⋅HOO . ) destabilize the transition state. Abstract : Role reversal : Hydroperoxyl radicals (HOO . ) are able to recycle an α‐tocopherol analogue, increasing the inhibition period up to 10 times, and exhibit a strong kinetic solvent effect arising from noncovalent interactions between HOO . and H‐bond‐accepting solvents.